Kinetic Study on Vanadium Recovery From Oil Fired Power Stations - Shanshool, Jabber; Mousa, Khalid M.; Obaid, Rana K. (Nahrain University College of Engineering Journal, 2009)
In this work it has been attempted to study the kinetic of vanadium recovery from fly ash by leaching with NaOH solution from previous work of Mosa (1999). The selected data were chosen at particle size of scale between 125 to 200 ?m, temperature 343 to 373 K, reaction (leaching) time up to 8 hours and at about fixed NaOH solution molarity (3 to 4 M).The results show that vanadium recovery increased with time and temperature and mostly decreased with particle size.A second order polynomial mathematical correlation was employed to describe vanadium recovery response. The correlation coefficient of the obtained correlation was 0.9990 and variance of 0.9981 with confidence levels of 95 %.Kinetic study shows that the chemical reaction is the controlling step which has the highest resistance among other steps. A chemical reaction order was found equals to -3 with activation energy of 1080 J/ mole and frequency factor of about 2.6884